PERBEDAAN HASIL BELAJAR MANAJEMEN TERPADU BALITA SAKIT (MTBS) MELALUI MEDIA PEMBELAJARAN VISUAL DAN AUDIOVISUAL - Munjidah, Annif (Jurnal Ilmiah Kesehatan, 2016)
Learning differences of integrated management of children sick (IMCI) Learning through Visual Media and Audiovisual. Integrated management of childhood illness is effective cost to solve toddler?s death that is caused by acute respiratory infections, diarrhea, measles, malaria, and malnutrition The students of midwifery as candidate of midwife must have good ability in integrated management of childhood illness. The purpose of this research is analysis study result of integrated management of childhood illness of learning media visual and audiovisual for students of Midwifery Diploma Degree Department FKK of UNUSA. This research used experimental analytic design by quasi experimental design ?after only with control quasi experimental?. The populations were all students of Midwifery Diploma Degree, faculty of medical sains Nahdatul Ulama University Surabaya are 177 students. The sampling technique used simple random sampling technique. The total of sample is 60 respondents that were divided into 30 respondents in treatment group and 30 respondents in control group. Data analysis used independent t test. There was the difference of study result statically significant between the students who got material by visual and audiovisual learning media. They who got material by audiovisual media had higher study result than those using visual media.